2018
DOI: 10.1093/nar/gky1162
|View full text |Cite
|
Sign up to set email alerts
|

Distributive enzyme binding controlled by local RNA context results in 3′ to 5′ directional processing of dicistronic tRNA precursors byEscherichia coliribonuclease P

Abstract: RNA processing by ribonucleases and RNA modifying enzymes often involves sequential reactions of the same enzyme on a single precursor transcript. In Escherichia coli, processing of polycistronic tRNA precursors involves separation into individual pre-tRNAs by one of several ribonucleases followed by 5′ end maturation by ribonuclease P. A notable exception are valine and lysine tRNAs encoded by three polycistronic precursors that follow a recently discovered pathway involving initial 3′ to 5′ directional proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…In contrast to RNase E where endonucleolytic cleavages in A/U rich regions of the single‐stranded RNAs (McDowall et al., 1994, 1995) can proceed either in the 5' → 3' direction (Richards & Belasco, 2019) or by a direct entry mechanism (Clarke et al., 2014; Garrey & Mackie, 2011; Kime et al., 2014), RNase P endonucleolytic cleavages proceed in the 3' → 5' direction, both in vivo and in vitro, based on the analysis of tRNA substrates (Agrawal et al., 2014; Zhao & Harris, 2019). Furthermore, the RNase P holoenzyme from both E. coli and Bacillus subtilis has been shown to cleave single‐stranded RNA in vitro with some sequence preferences, although much less efficiently compared with the structured RNAs (Hansen et al., 2001; Loria & Pan, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to RNase E where endonucleolytic cleavages in A/U rich regions of the single‐stranded RNAs (McDowall et al., 1994, 1995) can proceed either in the 5' → 3' direction (Richards & Belasco, 2019) or by a direct entry mechanism (Clarke et al., 2014; Garrey & Mackie, 2011; Kime et al., 2014), RNase P endonucleolytic cleavages proceed in the 3' → 5' direction, both in vivo and in vitro, based on the analysis of tRNA substrates (Agrawal et al., 2014; Zhao & Harris, 2019). Furthermore, the RNase P holoenzyme from both E. coli and Bacillus subtilis has been shown to cleave single‐stranded RNA in vitro with some sequence preferences, although much less efficiently compared with the structured RNAs (Hansen et al., 2001; Loria & Pan, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…but not the alaX pre-tRNAs with unprocessed 5′-leader sequences (the alaW and alaX intergenic sequences), in the strain containing the wild type RNase P (Figure 2b, lane 2; Figure 5, lane 2-3) indicated that the initial RNase P cleavage occurred at the alaX 5′-mature end separating the two pre-tRNAs following the removal of the Rho-independent transcription terminator by RNase E. The second RNase P cleavage occurred at the 5′-mature ends of alaW pre-tRNAs following the removal of its 3′ trailer sequences suggesting that the RNase P cleavage of alaW alaX transcript proceeds in a 3′ → 5′ direction (Figure 11). The 3′ → 5′ directionality of RNase P cleavages has been documented previously both in vivo (Agrawal et al, 2014) and in vitro (Zhao & Harris, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…Nonetheless, there is evidence that structural anti-determinants play a role in polycistronic ptRNA processing by E. coli RNase P. Remarkably, all seven valine tRNAs in E. coli require RNase P for separation from their primary polycistronic transcripts, which processes them in a 5′ to 3′ directional manner 59 . In the valVW operon a stem-loop in 5′ leader of tRNA valV inhibits RNase P cleavage resulting in enhanced cleavage of the 3’ most tRNA valW thus enforcing directional processing 24 , 60 . In the valU operon, the most 5′ ptRNA valU is processed last and has GG at N(−1)N(−2), the internal tRNA valX and tRNA valY have GU, while the 3′ tRNA lysV that is processed first has a near optimal UC dinucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…1a) 3,8 . These structural anti-determinants can involve the formation of stem loops in the 5′ leader 19,24 or pairing between the 3′ RCCA of tRNA and N(−1) to N(−3) 27,35,36 . To comprehensively identify and parse sequence determinants and anti-determinants in the 5′ leader, we used highthroughput sequencing kinetics (HTS-Kin) to measure the relative k cat /K m for all possible combinations of 5′ leader nucleotides N(−6) to N(−1) (n = 4096) [19][20][21]37 .…”
Section: Comprehensive Identification Of Ptrna 5′ Leader Determinants...mentioning
confidence: 99%
See 1 more Smart Citation